Approach to teaching programming in exact science careers - Nieves Rodríguez, Ana; Fernández, Patricia Mónica; Pérez, Adriana Inés; Isgro, Christine Adriane (I+ T+ C- Research, Technology and Science, 2019)
The University Programmer’s career, a short-term career, with practical implications, turned 20 years of existence in 2017. At the time of its creation, it promised to be a career with record of entrants within the Faculty of Exact Sciences and Technology of the National University of Tucuma?n. However, the desertion and abandonment of the career was felt, which generated that the donor team on impulse of the Academic Commission, make a thorough review of the contents of the subjects, the real needs of the companies in the environment, and that the way of imparting the contents is reconsidered. This article shows the experience of the subject Laboratory I, which is taught in the first semester of the first year of said career.